Resident involvement in upper extremity fracture fixation impacts surgical time and hospital stay - J. Pottanat, Paul; Zieminski, Colin; Allen, J. Ryan; Daly, Charles (International Journal of Research in Orthopaedics, 2025)
Background: The purpose of this study was to evaluate the impact of resident post graduate year (PGY) on surgical outcomes and operative time for upper extremity fracture fixation ad associated complications. Methods: Using the American college of surgeons’ national surgical quality improvement program (NSQIP) database, we conducted a query for all upper extremity fracture cases using current procedural terminology (CPT) codes outlined by the ACGME requirements for orthopaedic resident education. A total of 2,853 patients met inclusion criteria based on our initial query. Surgical complications and operative times were analyzed based on resident participation and PGY level. Linear regression models were used to assess the impact of resident training level on case duration and patient time in the OR. Results: Average total operative duration was significantly longer in cases with residents compared to cases without (average operative duration was 86.57 without a resident compared to 116.21 with resident(s), p<0.001). As PGY year increased, operative case duration also increased. Calculations of change in operative duration per PGY year. Proximal humerus fractures 9.975-minute increase per year (p=0.042); Humeral Shaft Fractures 9.933-minute increase per year (p=0.023); elbow 7.558-minute increase (p=0.011); distal radius 2.969-minute increase per year (p=0.038). Resident involvement was also associated with an increased risk for intraoperative transfusions (p=0.019) but not with any other surgical complications. Conclusions: For upper extremity fractures, there was a predictable increase in total operative time as PGY year increased. Resident involvement led to increased operative duration and patient time in the operating room.